Questioning Desire, Women, and Meaning in Popular Novel Cursed Bread (2023): Representation Analysis - Anam, Naufaludin (Universitas Airlangga, 2025)
This study is aimed to analyze and elaborate the issue about desire, woman, and the meaning represented in the popular novel. By conducting textual and audience analysis, researcher has an intention to seek for the connection and construction underlying the novel popularity and the representation follows. Stuart Hall representation theory is chosen for theoretical framework within the study. Taking into account of audiences in the form of responses or reviews toward the novel, researcher could apply it as supporting medium for data and elaboration on the study. Approach in textual analysis focus on the text and author, while audience analysis focus on the audiences’ response and drawing the connection to show the construction between them. The study applying descriptive qualitative model since the data collected from the analysis in form of narration. In collecting the data, researcher conducts comprehensive reading towards the novel and reviews from audiences and record or note any potential narration, points, and explanation which relates with the proposed issue. Analysis of the data by using Hall representation theory and hermeneutical analysis to draw the meaning and elaborating the linkage between variables. Result of the study showed that novel popularity is determined by the author’s choice in writing and audiences’ voice or response toward the novel. Another finding regarding with representation are: 1) desire representing human condition with its meaning and gender discourse agency, 2) women representation in popular fiction reflecting activism and emerging voice for counteract discourse also attracting readers and their reviews, 3) representation, text and audience formed tripartite connection for meaning construction.